Efficacy of Contact Lens Care Solutions in Removing Cholesterol Deposits From Silicone Hydrogel Contact Lenses. Issue 2 (March 2019) - Walther, Hendrik; Subbaraman, Lakshman N.; Jones, Lyndon
Abstract : Purpose: To determine the efficacy of multipurpose solutions (MPSs) on the removal of cholesterol deposits from silicone hydrogel (SH) contact lens materials using an in vitro model. Materials and Methods: Five SH lens materials: senofilcon A, comfilcon A, balafilcon A, lotrafilcon A, and lotrafilcon B were removed from the blister pack (n=4 for each lens type), incubated for 7 days at 37°C in an artificial tear solution containing 14 C radiolabeled cholesterol. Thereafter, lenses were stored in a preserved saline solution control (Sensitive Eyes Saline Plus) or cleaned with 1 of the 5 MPSs incorporating different preservatives (POLYQUAD/ALDOX, polyquaternium-1/alexidine, polyquaternium-1/PHMB, and 2 based on PHMB alone) using a rub and rinse technique, according to the manufacturer's recommendations, and stored in the MPS for a minimum of 6 hr. Lenses were then extracted with 2:1 chloroform:methanol, analyzed in a beta counter, and μg/lens of cholesterol was determined. Results: Balafilcon A and senofilcon A lens materials showed the highest amounts of accumulated cholesterol (0.93±0.02 μg/lens; 0.95±0.01 μg/lens, respectively), whereas lotrafilcon A and lotrafilcon B deposited the lowest amounts (0.37±0.03 μg/lens; 0.47±0.12 μg/lens, respectively). For all lens materials, the MPS preserved with POLYQUAD/ALDOX removed more deposited cholesterol than any other test solution; however, the amount of removed cholesterol contamination from the individual contact lenses was only statistically significant for balafilcon A and senofilcon A ( P =0.006 and P =0.042, respectively). Sensitive eyes and the other evaluated MPSs showed no significant effect on cholesterol removal ( P >0.05). Conclusion: Cholesterol-removal efficacy varies depending on the combination of lens material and solution. Only 1 MPS showed a statistically significant reduction of cholesterol deposit for only 2 of the 5 tested lens materials.